2023
DOI: 10.1101/2023.02.28.23286578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An assessment of rates and covariates of mpox diagnosis and vaccination provides evidence to refine eligibility criteria for mpox vaccination among gay, bisexual and other men who have sex with men in the Netherlands

Abstract: BackgroundThe 2022 multicountry mpox outbreaks predominantly affected gay, bisexual and other men who have sex with men (GBMSM) in non-endemic countries. Mpox vaccination is most effective if targeting GBMSM most at risk. It is unknown to what extent eligibility criteria for vaccination align with evidence on risk factors for mpox in GBMSM.MethodsWe conducted an online self-report survey among GBMSM in the Netherlands between 29 July and 30 August 30, 2022, corresponding to the first month of the Dutch mpox va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“… a It was assumed that the number of casual partners of activity group i was at the beginning of the outbreak (as estimated from the data; see Table 2 ) and was reduced to after day , with sampled from the uniform distribution between 0 and 0.3. The maximum of 30% reduction was based on preliminary results from the survey “Monkeypox: a new challenge for your sex life” [ 9 , 26 , 27 ]and reports from club owners in Amsterdam who experienced reduced numbers of visitors in July 2022, with the reduction reaching its maximum at the end of July 2022 with approximately 30% fewer visitors (P. Zantkuijl, personal communication). b Change applied to both very low and fairly low activity groups.…”
Section: Methodsmentioning
confidence: 99%
“… a It was assumed that the number of casual partners of activity group i was at the beginning of the outbreak (as estimated from the data; see Table 2 ) and was reduced to after day , with sampled from the uniform distribution between 0 and 0.3. The maximum of 30% reduction was based on preliminary results from the survey “Monkeypox: a new challenge for your sex life” [ 9 , 26 , 27 ]and reports from club owners in Amsterdam who experienced reduced numbers of visitors in July 2022, with the reduction reaching its maximum at the end of July 2022 with approximately 30% fewer visitors (P. Zantkuijl, personal communication). b Change applied to both very low and fairly low activity groups.…”
Section: Methodsmentioning
confidence: 99%
“…Given the importance of MPXV infection for public health and the influence of social/behavioral aspects on its epidemiology, we performed a space‐time analysis of mpox cases in Pernambuco state, northeastern Brazil, and identified predictors associated with its positive diagnosis as well. To the best of our knowledge, rare studies have performed multivariate analyses and identified mpox‐related predictors 12 . In this perspective, our findings contribute to the surveillance of mpox cases, as well as to the management and public health measures against the recent outbreaks.…”
Section: Introductionmentioning
confidence: 69%
“…To the best of our knowledge, rare studies have performed multivariate analyses and identified mpox-related predictors. 12 In this perspective, our findings contribute to the surveillance of mpox cases, as well as to the management and public health measures against the recent outbreaks.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…The vaccination programme in the Netherlands continued in 2023 and took newly identified risk factors, such as visiting sex venues, into account. 34,35 Continued vaccination programmes are needed to offer vaccination to new people meeting the criteria for vaccination or recently arrived migrant GBMSM. Surveillance of mpox and evaluation of the vaccination programmes, including assessment of VE, are of critical importance to inform future mpox prevention and control.…”
Section: Discussionmentioning
confidence: 99%